2011
DOI: 10.1152/ajpheart.00060.2011
|View full text |Cite
|
Sign up to set email alerts
|

Postmaximal contraction blood volume responses are blunted in obese and type 2 diabetic subjects in a muscle-specific manner

Abstract: The purpose of this study was to determine whether there are differences in postisometric contraction blood volume and oxygenation responses among groups of type 2 diabetes mellitus (T2DM), obese, and lean individuals detectable using MRI. Eight T2DM patients were individually matched by age, sex, and race to non-T2DM individuals with similar body mass index (obese) and lean subjects. Functional MRI was performed using a dual-gradient-recalled echo, echo-planar imaging sequence with a repetition time of 1 s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…The current study extends these findings to adults over 60 and includes the posterior leg (SOL) as well as the AC. It is well documented that microvascular function can be influenced by BMI (32) and hypertension (11). To account for these factors in our study, we examined age-related BOLD differences in a BMI-matched subgroup without hypertension and the age effect remained significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study extends these findings to adults over 60 and includes the posterior leg (SOL) as well as the AC. It is well documented that microvascular function can be influenced by BMI (32) and hypertension (11). To account for these factors in our study, we examined age-related BOLD differences in a BMI-matched subgroup without hypertension and the age effect remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…those that cannot be resolved in MRI images (22, 24, 40). Reduced BOLD magnitude or prolonged BOLD time courses have been reported in obesity (32), peripheral arterial disease (10), and diabetics with microvascular complications (37). Muscle BOLD responses are also remarkably higher in young, endurance trained adults compared to sedentary adults (40, 41) highlighting the influence of physical activity on peripheral vascular function.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4. Using a different assessment, Sanchez et al demonstrated impaired skeletal muscle blood flow in T2D and obese-matched controls (56% lower MRI signal intensity with maximum voluntary isometric contraction) [71]. There is evidence for both structural and functional abnormalities contributing to decrease skeletal muscle blood flow in diabetes.…”
Section: Muscle Contribution To Exercise Dysfunction In T2dmentioning
confidence: 99%
“…Structural and functional changes in the microvasculature play a pivotal role in the pathogenesis of cardiovascular disease, hypertension, and diabetes (4,5). Therefore, muscle BOLD may be a powerful tool for measuring peripheral vascular function in individuals with peripheral arterial occlusive disease (6), obesity (7), and diabetes (7,8). Despite these advances, muscle BOLD imaging still suffers from relatively low signal-to-noise ratio (SNR) and an incomplete understanding of its biophysical basis.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the case in the brain, blood vessels in skeletal muscle are primarily oriented parallel to each other and to the muscle fibers (5), imparting an orientation-dependence to the extravascular BOLD effect. When muscle fibers are aligned parallel to B 0 , as is the case in many MRI experiments, the extravascular contribution to the BOLD effect at field strengths of 3T or lower is negligible (1,7,10). Conversely, at higher field strengths such as 7T, the T 2 * of blood (~9 ms; (11)) is several rimwa shorter than at 3T (12).…”
Section: Introductionmentioning
confidence: 99%